Association of only-child status and household pet ownership with attention-deficit/hyperactivity disorder among Chinese preschool children: a population-based study - Zhang, Yuying; Qiu, Shuangyan; Guo, Vivian Yawei; Chen, Weiqing; Han, Xiaomei; Yang, Weikang (Frontiers in Public Health, 2025)
BackgroundThe associations of only-child status and household pet ownership with the risk of attention-deficit/hyperactivity disorder (ADHD) are inconclusive, and the joint effects of only-child status and household pet ownership on ADHD have not been thoroughly investigated.MethodsA population-based study was conducted in 2021 involving preschool children aged 3–6 years attending kindergartens in Longhua District, Shenzhen, China. Parents were invited to complete questionnaires providing information on socio-demographic and family-environmental factors. ADHD symptoms were assessed using the 26-item Swanson, Nolan, and Pelham Rating Scale as reported by parents.ResultsThis study included 63,282 children (mean age: 4.86 ± 0.85 years, 53.6% boys), representing 72.6% of all preschool children in this district in 2021. Among them, 34.4% were only-child and 9.6% were identified as having ADHD. Only-child status was associated with an increased risk of ADHD [adjusted odds ratio: 1.30 (95%CI: 1.23–1.38). Compared to children without a pet (cats or dogs) at ages 0–3 years, pet ownership at ages only 0–1 year, only 1–3 years, and both ages were associated with increased odds of ADHD: 1.59 (1.30–1.95), 1.58 (1.28–1.93), and 1.66 (1.42–1.92), respectively, after controlling for potential confounders. A significant interaction between pet ownership at only 1–3 years and only-child status was observed (adjusted P for interaction = 0.028). Similar findings were observed when the analyses were performed separately for boys and girls.ConclusionBoth only-child status and household pet ownership are associated with an increased risk of ADHD; however, the detrimental effect of pet ownership appears to be mitigated among only children when pet exposure occurs at ages 1–3 years, providing new insight into reducing family-related risk factors of ADHD.